Laboratory manual for nursing health assessment : a best practice approach - Jensen, Sharon, 1955- (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"This full-color spiral-bound pocket guide provides quick access to all aspects of the nursing health history and physical examination. It includes a quick guide to assessing the hospitalized patient and key topics and questions for health promotion, common symptoms, and sentinel symptoms requiring immediate medical intervention. This clinical guide is a perfect companion to Jensen's Nursing Health Assessment: A Best Practice Approach"--Provided by publisher.